Political communication through the prism of social media : how are Lebanese political parties using Facebook in electoral campaigns? - Zebib, Chirinne (Penerbit Universiti Kebangsaan Malaysia, 2022)
The integration of social media in political communication has expanded significantly over recent years. This article focuses on how politicians are using Facebook in electoral campaigns. The main objective is to analyse the different functions ascribed to this digital platform in electoral communication. The present research studies the usage of Facebook by political parties in Lebanon during the parliamentary election of 2018 based on quantitative content analysis. All Facebook posts of three major political parties published during the electoral campaign were collected and examined. The results of the study reveal first that most parties were using Facebook in a unidirectional way; that is, only to disseminate information without giving any real value to users’ feedback. A prime example of this was how the Future Movement, a popular political party, made significant use of external links, and effective forms of controlled Facebook tools. This demonstrated how politicians aimed to contain and direct users to their preferred information flow. Second, emerging parties from the opposition tended to publish more negative and attack posts than incumbents. Third, the interactive tools of Facebook were used poorly. Fourth, there was, however, a relative difference with regards to political groups outside the formal institution of power, such as the Political Alliance “Kollouna Watani” who made better use of the interactive function. The main factors that could explain the findings are the historical background and path of the political parties as well as their position in or outside the government, the partisan and costly coverage of traditional media outlets, and the hybridisation of political communication.